The Role of Natural Capital in Surviving Periods of Crisis: A Case Study of the Nglanggeran Village Community - Lasti Nur Satiani; Titi Susilowati Prabawa; Aldi Herindra Lasso (Jurnal Manajemen Hutan Tropika, 2022)
The sustainability of tourism-based livelihoods can be threatened when a crisis occurs. Thus, people’s resilience during crisis is a significant factor for people to maintain livelihoods as it is a contributing mechanism for people to escape from crisis. This research examines how the Nglanggeran community sustains their livelihoods by utilizing their natural resources as a strategy to survive Covid-19 pandemic between 2020 to 2021. This study uses an ethnographic approach. The data collection process was carried out through participant observation and in-depth interviews with 14 former migrant workers and who now live in Nglanggeran village. The focus of the analysis in this study is the strategy of the Nglanggeran community in maintaining their livelihoods by utilizing their land. The analysis process uses thematic analysis. People who own paddy fields are more likely to survive than those who plant trees for timber on their land. What the Nglanggeran community does is important in maintaining their resilience and as a survival strategy for the local community. Tourism activities do not have to displace traditional livelihood activities on local people's land, rather land use can be optimized to support sustainable livelihoods. While they can optimalise land use, this does not increase their quality of life. They have survived but their livelihoods remain vulnerable.